High-sensitivity signal processing circuit integrated coil antenna sensor toward measurements of the water fraction in the oil-water two-phase flow - Qu, Zilian (2023)
The measurement of water fraction in the oil-water two-phase flow is important for the processing control of oil production. In this article, a coil antenna-based high-sensitivity inductive sensor is proposed to measure the water fraction in the oil-water two-phase flow in real time. It employs a wire-wound coil antenna, an associated signal processing circuit, and a sensor fixture to support and hold them. The change of water fraction in the flow causes the change in equivalent inductance of the coil antenna. By adding external capacitors to the coil antenna, a parallel inductance-capacitance resonant circuit is formed, and it efficiently converts the inductance change to the voltage change, which improves the measurement sensitivity. The specified signal processing circuit picks up the voltage change, realizes the ac/dc signal conversion, and amplifies dc small signals. Then, the measurement theory is analyzed, and the transduction model of coil inductance change to voltage output is given. To verify the proposed inductive sensor, a prototype is fabricated, and a measurement platform is built, in which the generated oil-water flow has a water fraction ranging from 0% to 100%. Experimental results show that the proposed inductive sensor can measure the water fraction in real time with a measurement resolution of 1% and a measurement standard deviation of less than 1.2%.